Pathogenetic mechanisms of comorbid anxiety disorders in persons with social anxiety disorder: the role of dysfunction cognitive schemes - AVRAMCHUK, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Anxiety disorders are one of the common categories of mental health problems characterized by a persistent debilitating feeling of anxiety, which is due mainly to unproductive expectations about potential challenges or threats. For example, for people with social anxiety disorder, the fear of social situations can feel so intense that it seems out of their control, leading to a tendency toward social isolation and complicating the recovery process. Methods. An empirical study was conducted between 2018 and 2022 among individuals (aged 18-40) with social anxiety disorder and with clinically significant symptoms of co-occurring anxiety disorders (including generalized anxiety disorder and symptoms of panic attacks) according to DSM-5 criteria - the main the group consisted of 651 people. All study participants participated voluntarily and provided informed consent. Results. Individuals with social anxiety disorder exhibit higher levels of clinical anxiety and general distress compared to controls. Significant differences in the intensity of early dysfunctional schemes were also found compared to the control group. Correlations between manifestations of dysfunctional schemas, levels of social anxiety and manifestations of comorbid psychopathology have been demonstrated. It has been suggested that the contribution of cognitive, emotional, and behavioral responses related to schemas such as social isolation/alienation, incompetence/failure anticipation, and catastrophe anticipation may explain the distribution of variability in social anxiety symptoms and comorbid anxiety symptoms. Conclusions. The analysis of the results of the empirical study confirms the close relationship between dysfunctional beliefs and the severity of anxiety psychopathology in individuals with social anxiety disorder. Considering the features of the functioning of deep beliefs about oneself and social interaction, structured into cognitive schemes, can contribute to a practical approach to therapy and improve the quality of life of persons with the specified symptoms. Further research can be directed at expanding the role of early dysfunctional schemes in the pathogenesis of comorbid conditions and the role of avoidance mechanisms in adapting to life circumstances.